Psychometric Properties of the Brazilian Version of the Quality of Dying and Death for Adult Family Members of ICU Patients - Benichel, Cariston Rodrigo [UNESP]; Meneguin, Silmara [UNESP]; Pollo, Camila Fernandes [UNESP]; Oliveira, Mariele Gobo [UNESP]; de Oliveira, Cesar (MDPI, 2023)
Death is a complex, subjective phenomenon that requires an understanding of experiences to be qualified to provide care during the end-of-life process. This study aimed to analyze the psychometric properties of the Portuguese version (Brazil) of the Quality of Dying and Death (QODD) scale on family members of patients who died in adult intensive care units. A methodological study was conducted with 326 family members of patients that died in three ICUs of public hospitals in the state of São Paulo, Brazil. For this study, the QODD 3.2a (25 items and six domains) was administered during the period from December 2020 to March 2022. The analysis was performed using the classic theory of the tests and the goodness of fit of the model was tested using confirmatory factor analysis. We have used Spearman’s correlation coefficients between the scores of the overall scale and domains. Cronbach’s alpha coefficient and the intraclass correlation coefficient (ICC) were used for the evaluation of internal consistency and temporal stability, respectively. The Horn’s parallel analysis indicated two factors that were not confirmed in the exploratory factor analysis. A single factor retained 18 of the initial 25 items and the analysis of the goodness of fit to the unidimensional model resulted in the following: CFI = 0.7545, TLI = 0.690, chi-squared = 767.33, df = 135, RMSEA = 0.121 with 90%CI, and p = 5.04409. The inter-item correlations indicated a predominance of weak correlations among the items of the instrument. The items with the largest number of moderate correlations were questions 13b, 9b, and 10b and a strong correlation was found between questions 15b and 16b. Cronbach’s alpha coefficient was 0.8 and the ICC was 0.9. The Quality of Dying and Death—Version 3.2a (intensive therapy) in Brazilian Portuguese has a unidimensional structure and acceptable reliability. However, it did not obtain a good fit to the proposed factorial model.
Keywords: death; intensive care units; psychometrics; validation studies